TPU composite film for polishing and grinding and preparation method thereof
By using a TPU composite film composed of a base layer, polyurethane coating, TPU film layer and lubricant, the existing polishing film cannot achieve simple operation, good polishing effect, low cost and pollution-free at the same time, and achieve an efficient and environmentally friendly polishing effect.
Patent Information
- Application Number
- CN202411660777.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The existing mobile phone bezel polishing film cannot achieve the requirements of simple operation, good polishing effect, low cost and pollution-free at the same time.
A TPU composite film including a substrate layer, a polyurethane coating, a TPU film layer and a protective release layer is adopted. The TPU film layer is prepared from TPU particles and combines a lubricant composed of polyoxypropylene polyoxyethylene glyceryl ether, magnesium stearate and fatty acid amide to provide good polishing effect and operability.
It achieves the advantages of good polishing effect, easy operation, low cost and environmental protection and pollution-free. It is suitable for a variety of mobile phone frame materials, improving the adaptability and efficiency of polishing.
Smart Images

Figure BDA0005143283680000061 
Figure BDA0005143283680000071 
Figure BDA0005143283680000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of TPU composite film processing, and more specifically, to a TPU composite film for polishing and grinding and a preparation method thereof. Background Art
[0002] The mobile phone frame needs to be ground and polished during processing to improve the glossiness and flatness of the frame to meet the requirements of visual aesthetics and durability. Currently, diamond polishing film, nano polishing film and chemical polishing film are mainly used. Among them, diamond polishing film uses diamond particles as abrasives, has extremely high hardness and strong wear resistance, can effectively remove defects and unevenness on the surface of the mobile phone frame, has high polishing efficiency, and the surface of the mobile phone frame after polishing has high gloss and flatness, and has good visual effects. However, the price of diamond polishing film is relatively high, and the polishing pressure and speed need to be precisely controlled to avoid excessive wear or damage to the mobile phone frame, which requires high skills of the operator; nano-polishing film uses nano-level abrasive particles for polishing, which can achieve extremely high polishing accuracy and make the surface of the mobile phone frame smoother and more delicate, but the price of nano-polishing film is also relatively high, and when using nano-polishing film for polishing, professional polishing equipment and operating skills are required to ensure the polishing effect; chemical polishing film removes oxides and stains on the surface of the mobile phone frame through chemical reaction, and achieves the polishing effect at the same time. The surface gloss after polishing is high, and it is relatively simple to use, without the need for complex equipment and operation, but the chemical polishing effect may be affected by the chemical reaction conditions, and the polishing consistency is difficult to ensure, and the adaptability of chemical polishing film is poor. Polishing of mobile phone frames of different materials may not achieve the expected polishing effect.
[0003] In summary, there is no polishing film in the prior art that is easy to operate, has a good polishing effect, is low-cost and pollution-free. Summary of the invention
[0004] In order to solve the problem that the existing mobile phone frame polishing film cannot have simple operation, good polishing effect, low cost and no pollution at the same time, the present application provides a TPU composite film for polishing and grinding and a preparation method thereof.
[0005] In the first aspect, the present application provides a TPU composite film for polishing and grinding, adopting the following technical scheme: a TPU composite film for polishing and grinding, comprising a substrate layer, a polyurethane coating, a TPU film layer and a protective release layer in sequence, wherein the TPU film layer is prepared from TPU particles.
[0006] By adopting the above technical solution, the prepared TPU composite film can provide the advantages of good polishing effect, easy operation, low cost and environmental protection.
[0007] Preferably, the TPU film layer is prepared from the following raw materials in parts by weight: TPU95-98 parts 2-8 parts of lubricant The lubricant is composed of polyoxypropylene polyoxyethylene glycerol ether, magnesium stearate and fatty acid amide.
[0008] By adopting the above technical solution, the prepared TPU composite film can provide the advantages of good polishing effect, easy operation, low cost and environmental protection.
[0009] The TPU film layer in this application is used for polishing because TPU has good wear resistance. With TPU as the main component, the wear resistance of the TPUT film layer can be improved, so that the composite film can maintain a flat surface for a long time during the polishing and grinding process and is not easy to wear. At the same time, TPU has good elasticity, so that the composite film can quickly recover its deformation when subjected to external force, thereby maintaining a stable polishing and grinding effect. In addition, TPU shows good stability to a variety of chemical substances and is not easily corroded by acids, alkalis and other substances, ensuring that the composite film can be applied to a variety of polishing liquids and can be used for a long time in complex environments. By using the substrate layer to support the TPU film layer, the composite film is prevented from being deformed or damaged during the polishing process, thereby maintaining the consistency of the polishing effect and facilitating the polishing of the TPU film layer. The polyurethane coating is used to fix the substrate layer and the TPU layer to prevent the two from separating.
[0010] The lubricant in the TPU composite film is composed of polyoxypropylene polyoxyethylene glycerol ether, magnesium stearate and fatty acid amide, which can be evenly distributed on the polishing surface, providing a stable lubrication effect, thereby ensuring the consistency of polishing, while reducing the friction resistance during the polishing process, making polishing easier, thereby improving the polishing efficiency. Polyoxypropylene polyoxyethylene glycerol ether has good lubricity and dispersibility, which can reduce the friction coefficient between the TPU film layer and the polished surface, and reduce the generation of heat and wear; magnesium stearate has lubrication and demoulding effects, and can form a lubricating film between the TPU film layer and the polished surface, further reducing friction, and helping to prevent the film layer from sticking during the polishing process; fatty acid amide has excellent lubricity and wear resistance, which can enhance the wear resistance of the TPU film layer, while providing additional lubrication effect, making the polishing process smoother.
[0011] The design of the TPU composite film of the present application does not rely on complex polishing equipment or highly professional operating skills. Its softness and elasticity make the polishing process smoother and reduce the need for precise control of polishing pressure and speed. When in use, you only need to connect the substrate layer to the polishing wheel to use it. If Velcro is used, the hairy side of the Velcro is bonded to the substrate layer, the hook side of the Velcro is connected to the polishing wheel, and then the hairy side and the hook side are fitted to complete the assembly of the TPU composite film for polishing and grinding, which is convenient and fast and does not require specific equipment. When in use, the polishing liquid is sprayed onto the TPU film layer, and then the TPU film layer is used to polish the mobile phone frame. The TPU composite film has a strong adaptability to different materials, so that the composite film can be applied to a variety of mobile phone frame materials, improving the adaptability of polishing.
[0012] The TPU composite film used in the present application has lower cost than diamond polishing film and nano-polishing film.
[0013] Preferably, the weight ratio of the polyoxypropylene polyoxyethylene glycerol ether, the magnesium stearate and the fatty acid amide is 3:(5-6):1.
[0014] By adopting the above technical solution, the dosage of polyoxypropylene polyoxyethylene glycerol ether, magnesium stearate and fatty acid amide is optimized, the polishing efficiency of the mobile phone frame is further improved, the consistency and uniformity of the polishing are enhanced, and at the same time, the film can be applied to a variety of mobile phone frame materials, thereby improving the adaptability of polishing.
[0015] Preferably, the TPU film layer further comprises 5-10 parts by weight of nano solid filler.
[0016] By adopting the above technical solution, the polishing effect of the TPU composite film when polishing the mobile phone frame can be further improved. The nano solid filler has extremely high hardness and wear resistance, which can improve the hardness and wear resistance of the TPU film layer, so that the TPU composite film can better resist wear during the polishing process and extend its service life. At the same time, the tiny size of the nano solid filler enables it to fill the tiny pores in the TPU film layer, making the surface of the film layer smoother, which helps to improve the polishing accuracy and make the surface of the polished mobile phone frame smoother and more delicate.
[0017] Preferably, the nano solid filler is composed of nano silicon carbide, nano silicon nitride and nano magnesium silicate in a weight ratio of (4-5):2:(3-6).
[0018] By adopting the above technical solution, the type and amount of nano solid fillers are optimized, the efficiency and precision of TPU composite film in polishing mobile phone frames are further improved, and the hardness and wear resistance of TPU film layer are improved, making it more durable and scratch-resistant, and extending the service life of TPU film. Among them, nano silicon carbide and nano silicon nitride both have high hardness and high wear resistance, and can quickly remove flaws and unevenness on the surface of mobile phone frames, thereby improving polishing efficiency. The addition of nano magnesium silicate further enhances the dispersion and stability of fillers, ensuring the uniformity and consistency of the polishing process.
[0019] Preferably, the polyurethane coating is obtained by coating polyurethane glue on the surface of the substrate layer, and the polyurethane glue is prepared from the following raw materials in parts by weight: Polyether polyol 20-25 parts Polyester polyol 15-20 parts 10-15 parts of diphenylmethane diisocyanate 1-2 parts of curing agent Chain extender 0.8-1.2 parts Catalyst 0.5-1 part 1-2 parts surfactant 30-40 parts of organic solvent Modifier 5-9 parts The modifier consists of epoxy resin, organic sulfonate and hydroxyethyl cellulose.
[0020] By adopting the above technical solution, the substrate layer and the TPU film layer are stably connected, ensuring that the TPU layer and the substrate layer are not separated during the grinding process, and improving the polishing effect and polishing efficiency. The material used for the substrate layer is different from the material used for the TPU film layer, so that when the surface energy, polarity or chemical composition of the substrate layer and the TPU layer are greatly different, the adhesion between them may be weakened, and the bonding between the two is unstable. In this application, the polyurethane prepared by adopting the above formula has good wettability, can fully penetrate into the tiny pores of the substrate layer and the TPU layer, form a tight adhesion layer, and improve the connection stability of the substrate layer and the TPU layer.
[0021] In this application, polyether polyol, polyester polyol, diphenylmethane diisocyanate and catalyst are combined to generate polyurethane prepolymer, so that the polyurethane coating has both sufficient flexibility and excellent adhesion performance, and can be closely attached to the substrate layer and the TPU film layer. Surfactants can reduce the surface tension between the polyurethane glue and the substrate layer and the TPU film layer, promote the wetting and spreading of the glue, help increase the contact area between the coating and the substrate layer and the TPU film layer, and improve adhesion. Organic solvents can dilute the polyurethane glue, reduce its viscosity, and facilitate coating and processing.
[0022] The TPU film will generate heat due to friction during the grinding process, which will cause the bonding performance of the substrate layer and the TPU layer to decrease, affecting the polishing effect of the TPU film, and its service life is greatly reduced. In this regard, the heat resistance of the polyurethane glue is further improved by adding epoxy resin in the present application, and the bonding performance of the polyurethane glue can also be improved. Hydroxyethyl cellulose has good thickening and tackifying effects, which can increase the viscosity of the polyurethane glue, making it easier to penetrate into the micropores of the substrate and the TPU film, forming a tight connection. That is, the synergistic effect of epoxy resin and hydroxyethyl cellulose can improve the adhesion of the polyurethane glue, so that it can achieve stable connection on various substrates and TPU films. Organic sulfonates can improve the wettability and dispersibility of polyurethane glue, and help polyurethane glue to form a uniform coating on the substrate.
[0023] Preferably, the polyurethane glue is prepared by the following method: A: vacuum dry the polyether polyol and polyester polyol at 100-110°C, then cool to 65-75°C, add diphenylmethane diisocyanate and then drop the catalyst, heat to 90-95°C and react for 2-4h, add the chain extender and react for 1-2h, cool to 20-30°C to obtain a polyurethane prepolymer; B: Mix the organic solvent and the modifier, then add the curing agent, the surfactant and the polyurethane reactant, stir and mix to obtain the polyurethane glue.
[0024] By adopting the above technical scheme, polyether polyol, polyester polyol, diphenylmethane diisocyanate and catalyst are fully reacted to form a polyurethane prepolymer with good viscosity. The steps of vacuum drying and temperature control of polyether polyol and polyester polyol effectively avoid the influence of side reactions and impurities, thereby improving the stability of the glue. Mixing the organic solvent and the modifier can ensure the uniform dispersion of the modifier in the solvent. By stirring and mixing, the uniform dispersion and full reaction of all components in the solvent can be ensured to form a stable polyurethane glue with excellent performance.
[0025] Preferably, the weight ratio of the epoxy resin, the organic sulfonate and the hydroxyethyl cellulose is 4:(0.5-0.8):2.
[0026] By adopting the above technical scheme, the dosage of epoxy resin, organic sulfonate and hydroxyethyl cellulose is optimized, and the heat resistance, adhesion and wettability of the polyurethane glue are further improved, making it easier to coat and bond.
[0027] Preferably, the thickness of the substrate layer is 0.01-0.2 mm, the thickness of the polyurethane coating is 0.001-0.06 mm, and the thickness of the TPU is 0.01-0.2 mm.
[0028] By adopting the above technical solution, the thickness of the substrate layer, polyurethane coating and TPU is optimized to ensure the uniform transmission of polishing force and uniform polishing effect during the polishing process, which helps to reduce scratches, pits and other defects generated during the polishing process and improve the surface gloss and flatness after polishing. The thicker substrate layer and the appropriate amount of polyurethane coating provide good protection and support, making the TPU composite film less prone to wear or damage during the polishing process, extending the service life of the polishing film and reducing the replacement frequency and cost.
[0029] Preferably, the substrate layer is one of a PET substrate layer, a PP substrate layer, a PC substrate layer or a PBT substrate layer.
[0030] By adopting the above technical solution, the type of substrate layer is optimized, the durability and support of the substrate layer are improved, and the substrate layer can withstand the friction and wear during the polishing process. In addition, the above substrate layers have a wide range of adaptability and can be applied to the polishing needs of mobile phone frames of different materials, shapes and sizes.
[0031] In a second aspect, the present application provides a method for preparing a TPU composite film for polishing and grinding, using the following technical solution: A method for preparing a TPU composite film for polishing and grinding comprises the following preparation steps: S1, applying polyurethane glue on the surface of the substrate layer and curing it to form a polyurethane coating; S2, mixing TPU and lubricant to obtain a mixture, and then adding it into a screw extruder to melt, and the molten mixture flows to the surface of the polyurethane coating through a die molding, and then cooled, and then a release protective film is attached to the surface of the TPU layer to obtain a TPU composite film for polishing and grinding.
[0032] By adopting the above technical solution, the polyurethane glue is coated on the surface of the substrate layer and solidified, and a uniform and dense polyurethane coating can be quickly formed, which not only improves the bonding strength between the substrate layer and the TPU layer, but also enhances the overall structural stability of the composite film. After the TPU and lubricant are mixed, they are melted and extruded through a screw extruder. The molten mixture flows to the surface of the polyurethane coating through a die molding, achieving uniform distribution and close fit of the TPU layer, improving the molding efficiency of the TPU layer, and ensuring the surface flatness of the composite film. Affixing a release protective film to the surface of the TPU layer can effectively prevent the composite film from being contaminated or damaged during subsequent processing or storage.
[0033] In summary, this application has the following beneficial effects: 1. The TPU composite film in this application combines the stability of the substrate layer, the adhesion of the polyurethane coating, and the wear resistance of the TPU film layer to ensure the high efficiency and durability of the TPU composite film during the polishing and grinding process. Among them, the TPU film layer uses TPU as the main component and has excellent wear resistance, so that the composite film can maintain a flat surface for a long time during the polishing and grinding process and is not easy to wear. At the same time, the TPU material has good elasticity, so that the composite film can quickly restore deformation when subjected to external force, thereby maintaining a stable polishing and grinding effect. By using a lubricant composed of polyoxypropylene polyoxyethylene glycerol ether, magnesium stearate and fatty acid amide, the friction coefficient between the composite film and the polishing and grinding surface can be reduced, thereby reducing wear and improving polishing and grinding efficiency. DETAILED DESCRIPTION
[0034] Preparation Example The epoxy resin was purchased from Anhui Xinyuan Technology Co., Ltd., model number is XY128L.
[0035] Polyether polyol was purchased from Jiangsu Rayne Environmental Protection Technology Co., Ltd., model MN-700.
[0036] Polyester polyol was purchased from Shanghai Hongzhuang Chemical Technology Co., Ltd., model number is C10H20O6.
[0037] Preparation Example 1 A polyurethane glue is prepared by the following method: A: 200 g of polyether polyol and 150 g of polyester polyol were vacuum dried at 100° C., then cooled to 65° C., 100 g of diphenylmethane diisocyanate was added, and then 5 g of catalyst (dibutyltin dilaurate) was added dropwise, the temperature was raised to 90° C. for reaction for 2 h, 8 g of chain extender (neopentyl glycol) was added for reaction for 1 h, and the temperature was lowered to 20° C. to obtain a polyurethane reactant; B: Mix 300 g of organic solvent (ethyl acetate) and 50 g of modifier, then add 10 g of curing agent (triethylenetetramine), 10 g of surfactant (dodecyl ammonium bromide) and polyurethane reactant, stir and mix to obtain polyurethane glue.
[0038] The modifier is composed of epoxy resin, organic sulfonate (sodium lignin sulfonate) and hydroxyethyl cellulose in a weight ratio of 4:0.5:2.
[0039] The difference between Preparation Example 2-3 and Preparation Example 1 is that the types of raw materials, amounts and experimental parameters for preparing the polyurethane glue are different. The specific differences are shown in Table 1: Table 1 Raw material types, amounts and experimental parameters for preparing polyurethane glue in Preparation Examples 1-3 The modifier in Preparation Example 2 is composed of epoxy resin, organic sulfonate (sodium p-aminobenzenesulfonate) and hydroxyethyl cellulose in a weight ratio of 4:0.6:2.
[0040] The modifier in Preparation Example 3 is composed of epoxy resin, organic sulfonate (sodium pyridine toluenesulfonate) and hydroxyethyl cellulose in a weight ratio of 4:0.8:2.
[0041] Preparation Example 4 A polyurethane glue, the difference between this preparation example and preparation example 1 is that the weight ratio of epoxy resin, organic sulfonate (sodium lignin sulfonate) and hydroxyethyl cellulose is 2:0.5:2.
[0042] Preparation Example 5 A polyurethane glue, the difference between this preparation example and preparation example 1 is that the weight ratio of epoxy resin, organic sulfonate (sodium lignin sulfonate) and hydroxyethyl cellulose is 2:0.5:4.
[0043] Preparation Example Preparation Comparative Example 1 A polyurethane glue, the difference between this preparation comparative example and preparation example 1 is that the modifier is composed of epoxy resin and organic sulfonate in a weight ratio of 4:0.5.
[0044] Preparation Comparative Example 2 A polyurethane glue, the difference between this preparation comparative example and preparation example 1 is that the modifier is composed of epoxy resin and hydroxyethyl cellulose in a weight ratio of 4:2.
[0045] Preparation Comparative Example 3 A polyurethane glue, the difference between this preparation comparative example and preparation example 1 is that the modifier is composed of organic sulfonate and hydroxyethyl cellulose in a weight ratio of 0.5:2.
[0046] Preparation Comparative Example 4 A polyurethane glue, the difference between this preparation comparative example and preparation example 1 is that acrylic resin is used instead of a modifier.
[0047] Acrylic resin was purchased from Shandong Huling New Materials Co., Ltd., model PT-2060A. Example
[0048] The PET substrate layer was purchased from Liheng New Materials Technology (Guangdong) Co., Ltd., model number L-6100.
[0049] TPU was purchased from Dongguan Zhenpin New Materials Co., Ltd. The brand is BASF of Germany and the grade is 1190A.
[0050] Example 1 A TPU composite film for polishing and grinding is prepared by the following method: S1. Apply polyurethane glue on the surface of the substrate layer (PET substrate layer) with a coating weight of 10g / m 2 , curing to form a polyurethane coating; S2. Mix 990 g of TPU to obtain a mixture, then add it into a screw extruder to melt it. The molten mixture flows to the surface of the polyurethane coating through a die molding, and then cools it. Then, a release protective film is attached to the surface of the TPU layer to obtain a TPU composite film for polishing and grinding.
[0051] Example 2 A TPU composite film for polishing and grinding is prepared by the following method: S1. Apply polyurethane glue on the surface of the substrate layer (PET substrate layer) with a coating weight of 10g / m 2 , curing to form a polyurethane coating; S2. Mix 950 g of TPU and 40 g of lubricant to obtain a mixture, and then add it into a screw extruder to melt. The molten mixture flows to the surface of the polyurethane coating through a die molding, and is cooled. Then, a release protective film is attached to the surface of the TPU layer to obtain a TPU composite film for polishing and grinding.
[0052] The lubricant is composed of polyoxypropylene polyoxyethylene glycerol ether, magnesium stearate and fatty acid amide in a weight ratio of 3:5:1.
[0053] The thickness of the substrate layer was 0.01 mm, the thickness of the polyurethane coating was 0.001 mm, and the thickness of the TPU was 0.01 mm.
[0054] The difference between Example 3-4 and Example 2 is that the raw material types, amounts and experimental parameters for preparing the TPU composite film for polishing and grinding are different. The specific differences are shown in Table 2: Table 2 Raw material types, amounts and experimental parameters for preparing TPU composite films for polishing and grinding in Examples 2-4 In Example 3, the lubricant is composed of polyoxypropylene polyoxyethylene glycerol ether, magnesium stearate and fatty acid amide in a weight ratio of 3:5.5:1. The thickness of the substrate layer is 0.1 mm, the thickness of the polyurethane coating is 0.03 mm and the thickness of the TPU is 0.1 mm.
[0055] In Example 4, the lubricant is composed of polyoxypropylene polyoxyethylene glycerol ether, magnesium stearate and fatty acid amide in a weight ratio of 3:6:1. The thickness of the substrate layer is 0.2 mm, the thickness of the polyurethane coating is 0.06 mm and the thickness of the TPU is 0.2 mm.
[0056] Example 5 A TPU composite film for polishing and grinding. The difference between this embodiment and embodiment 1 is that: in step S2, 950g of TPU, 40g of lubricant and 50g of nano solid filler (nano silicon carbide) are mixed.
[0057] Example 6 A TPU composite film for polishing and grinding. The difference between this embodiment and embodiment 1 is that: in step S2, 950 g of TPU, 40 g of lubricant and 100 g of nano solid filler (nano silicon carbide) are mixed.
[0058] Example 7 A TPU composite film for polishing and grinding. The difference between this embodiment and embodiment 4 is that the nano solid filler is composed of nano silicon carbide, nano silicon nitride and nano magnesium silicate in a weight ratio of 4:2:3.
[0059] Example 8 A TPU composite film for polishing and grinding. The difference between this embodiment and embodiment 4 is that the nano solid filler is composed of nano silicon carbide, nano silicon nitride and nano magnesium silicate in a weight ratio of 5:2:6.
[0060] Example 9 A TPU composite film for polishing and grinding. The difference between this embodiment and Example 1 is that the polyurethane glue comes from Preparation Example 4.
[0061] Example 10 A TPU composite film for polishing and grinding. The difference between this embodiment and Example 4 is that the polyurethane glue comes from Preparation Example 5.
[0062] Embodiment 11 A TPU composite film for polishing and grinding. The difference between this embodiment and embodiment 4 is that the polyurethane glue comes from comparative preparation example 1.
[0063] Example 12 A TPU composite film for polishing and grinding. The difference between this embodiment and Example 1 is that the polyurethane glue comes from Comparative Preparation Example 2.
[0064] Example 13 A TPU composite film for polishing and grinding. The difference between this embodiment and Example 1 is that the polyurethane glue comes from Comparative Preparation Example 3.
[0065] Embodiment 14 A TPU composite film for polishing and grinding. The difference between this embodiment and Example 1 is that the polyurethane glue comes from Comparative Preparation Example 4.
[0066] Comparative Example Comparative Example 1 A TPU composite film for polishing and grinding. The difference between this embodiment and embodiment 1 is that the first step is omitted, and a TPU layer is directly formed on the surface of a PET substrate in step S2.
[0067] Comparative Example 2 A TPU composite film for polishing and grinding. The difference between this embodiment and embodiment 2 is that the lubricant is composed of polyoxypropylene polyoxyethylene glycerol ether, magnesium stearate and fatty acid amide in a weight ratio of 3:5.
[0068] Comparative Example 3 A TPU composite film for polishing and grinding. The difference between this embodiment and embodiment 2 is that the lubricant is composed of magnesium stearate and fatty acid amide in a weight ratio of 5:1.
[0069] Comparative Example 4 A TPU composite film for polishing and grinding. The difference between this embodiment and embodiment 2 is that the lubricant is composed of polyoxypropylene polyoxyethylene glycerol ether and fatty acid amide in a weight ratio of 3:1.
[0070] Detection method / test method Polishing rate test: A UNIPOL-1200S CMP test machine was used to perform a polishing test. The TPU composite films used for polishing and grinding in Examples 1-14 and Comparative Examples 1-4 were installed on a polishing wheel. The polishing liquid used was ultrafine high-purity cerium dioxide polishing liquid (purchased from Zhejiang Manli Nanotechnology Co., Ltd.). The polishing pad had a diameter of 200 mm, and the polishing sample was an iron sheet with a diameter of 2 inches. The polishing parameters are as follows: polishing pressure 3 psi, polishing speed 110 rpm, polishing liquid flow rate 100 mL / min, and polishing time 10 min.
[0071] The mass of the iron sheet before and after polishing was weighed using a METTLER TOLETO precision electronic balance to calculate the material removal rate during polishing, i.e. the polishing rate. The material removal rate is defined as the thickness of material removed by polishing per unit time, and the calculation formula is as follows: Polishing rate (nm / min) = (W0-Wi) / (pw*Sw*t)*10 7 Where W0 is the mass of the iron sheet before polishing (g), W i is the mass of the iron sheet after polishing (g), p w is the density of the iron sheet material (g / cm3), Sw is the surface area of the iron sheet (cm 2 ), t is the polishing time (min).
[0072] Adaptability test: prepare polishing samples of glass sheets, plastic sheets, stainless steel sheets, copper-aluminum alloy sheets and iron sheets respectively, and use the TPU composite films for polishing and grinding prepared in Examples 1-15 and Comparative Examples 1-4 respectively to polish the samples according to the polishing rate test method, and observe whether the surfaces of the glass sheets, plastic sheets, stainless steel sheets, copper-aluminum alloy sheets and iron sheets are smooth and flat.
[0073] Test of adhesion stability between substrate layer and TPU film layer: A polishing experiment was carried out using a UNIPOL-1200S CMP test machine. The TPU composite films used for polishing and grinding in Examples 1-14 and Comparative Examples 1-4 were installed on a polishing wheel. The polishing liquid used was ultrafine high-purity cerium dioxide polishing liquid (purchased from Zhejiang Manli Nanotechnology Co., Ltd.). The polishing pad had a diameter of 200 mm, and the polishing sample was an iron sheet with a diameter of 2 inches. The polishing parameters are as follows: polishing pressure 3 psi, polishing speed 50 rpm, polishing liquid flow rate 100 mL / min.
[0074] Grinding was performed according to the above parameters. After 5 hours of grinding, the TPU composite film used for polishing was placed in the red solution and soaked for ten minutes every 2 hours. It was taken out and observed whether there was red liquid between the substrate layer and the TPU film layer. If there was, the test was stopped and the time when the red liquid appeared was counted (5+2n). The experimental data are shown in Table 3: Table 3 Experimental data of Examples 1-13 and Comparative Examples 1-4 Comparing Example 1 with Comparative Example 1, the polishing rate in Comparative Example 1 is lower than that in Example 1, and red liquid appears in 9 hours in the bonding stability test between the substrate layer and the TPU film layer, indicating that the TPU composite film for polishing and grinding with a specific structure prepared by the process in the present application has good polishing effect and structural stability. Comparing Example 2 with Comparative Example 1, the polishing rate in Comparative Example 1 is lower than that in Example 1, and red liquid appears in 9 hours in the bonding stability test between the substrate layer and the TPU film layer, indicating that the TPU composite film for polishing and grinding with a specific structure prepared by the process in the present application has good polishing effect and structural stability.
[0075] Comparing Example 2 with Comparative Examples 2-3, the polishing rate in Comparative Examples 2-3 is lower than that in Example 1, and red liquid appears in 19 hours in the bonding stability test between the substrate layer and the TPU film layer; in Comparative Examples 2-3, the surface of the glass sheet, the surface of the copper-aluminum alloy sheet, and the surface of the plastic sheet are respectively rough, indicating that by preparing a lubricant with polyoxypropylene polyoxyethylene glycerol ether, magnesium stearate and fatty acid amide, and then preparing the TPU film layer, the polishing effect, structural stability and adaptability of the TPU composite film used for polishing and grinding can be further improved.
[0076] Comparing Example 2 with Example 5-6, the polishing rate in Example 5-6 is higher than that in Example 2, indicating that the polishing effect of the TPU composite film used for polishing and grinding can be further improved by adding nano solid fillers.
[0077] Comparing Example 5 with Examples 7-8, the polishing rate in Examples 7-8 is higher than that in Example 5, indicating that the polishing effect of the TPU composite film used for polishing and grinding can be further improved by optimizing the type and amount of nano solid filler.
[0078] Comparing Example 1 with Examples 8-9, the polishing rate in Examples 8-9 is higher than that in Example 1, and red liquid appeared after 23 hours in the bonding stability test between the substrate layer and the TPU film layer, indicating that the polishing effect and structural stability of the TPU composite film used for polishing and grinding can be further improved by optimizing the dosage of epoxy resin, organic sulfonate and hydroxyethyl cellulose.
[0079] Comparing Example 2 with Examples 11-14, the polishing rate in Examples 11-14 is lower than that in Example 2, and red liquid appears in less than 19 hours in the bonding stability test of the substrate layer and the TPU film layer, indicating that the polyurethane glue prepared by the present application can effectively improve the polishing effect and structural stability of the TPU composite film used for polishing and grinding.
[0080] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A TPU composite film for polishing and grinding, characterized in that: It comprises a substrate layer, a polyurethane coating, a TPU film layer and a protective release layer in sequence, wherein the TPU film layer is prepared from TPU particles.
2. A TPU composite film for polishing and grinding according to claim 1, characterized in that: The TPU film layer is prepared from the following raw materials in parts by weight: TPU95-98 parts 2-8 parts of lubricant The lubricant is composed of polyoxypropylene polyoxyethylene glycerol ether, magnesium stearate and fatty acid amide, and the weight ratio of the polyoxypropylene polyoxyethylene glycerol ether, the magnesium stearate and the fatty acid amide is 3: (5-6):
1.
3. A TPU composite film for polishing and grinding according to claim 2, characterized in that: The TPU film layer further comprises 5-10 parts by weight of nano solid filler.
4. The TPU composite film for polishing and grinding according to claim 3, characterized in that: The nano solid filler is composed of nano silicon carbide, nano silicon nitride and nano magnesium silicate in a weight ratio of (4-5):2:(3-6).
5. The TPU composite film for polishing and grinding according to claim 2, characterized in that: The polyurethane coating is obtained by coating the polyurethane glue on the surface of the substrate layer, and the polyurethane glue is prepared from the following raw materials in parts by weight: Polyether polyol 20-25 parts Polyester polyol 15-20 parts 10-15 parts of diphenylmethane diisocyanate 1-2 parts of curing agent Chain extender 0.8-1.2 parts Catalyst 0.5-1 part 1-2 parts surfactant 30-40 parts of organic solvent Modifier 5-9 parts The modifier consists of epoxy resin, organic sulfonate and hydroxyethyl cellulose.
6. A TPU composite film for polishing and grinding according to claim 5, characterized in that: The polyurethane glue is prepared by the following method: A: vacuum dry the polyether polyol and polyester polyol at 100-110°C, then cool to 65-75°C, add diphenylmethane diisocyanate and then drop the catalyst, heat to 90-95°C and react for 2-4h, add the chain extender and react for 1-2h, cool to 20-30°C to obtain a polyurethane prepolymer; B: Mix the organic solvent and the modifier, then add the curing agent, the surfactant and the polyurethane reactant, stir and mix to obtain the polyurethane glue.
7. The TPU composite film for polishing and grinding according to claim 5, characterized in that: The weight ratio of the epoxy resin, the organic sulfonate and the hydroxyethyl cellulose is 4:(0.5-0.8):
2.
8. The TPU composite film for polishing and grinding according to claim 1, characterized in that: The thickness of the substrate layer is 0.01-0.2 mm, the thickness of the polyurethane coating is 0.001-0.06 mm, and the thickness of the TPU is 0.01-0.2 mm.
9. The TPU composite film for polishing and grinding according to claim 1, characterized in that: The substrate layer is one of a PET substrate layer, a PP substrate layer, a PC substrate layer or a PBT substrate layer.
10. A method for preparing a TPU composite film for polishing and grinding as claimed in any one of claims 1 to 9, characterized in that: The method comprises the following preparation steps: S1, applying polyurethane glue on the surface of the substrate layer and curing it to form a polyurethane coating; S2, mixing TPU and lubricant to obtain a mixture, and then adding it into a screw extruder to melt, the molten mixture flows to the surface of the polyurethane coating through a die molding, and then cooled, and then a release protective film is attached to the surface of the TPU layer to obtain a TPU composite film for polishing and grinding.
Citation Information
Patent Citations
Polishing pad and method for producing polishing pad
CN104321370A
Composite base material polishing grinding apparatus and preparing method thereof
CN107344336A
Novel wet and dry dual-purpose polishing grinding tool and preparation method thereof
CN112059936A
Polishing layer for preparing polishing pad as well as preparation method and application of polishing layer
CN116872080A
Elastic TPU Polishing Composite Membrane and Polishing Tool therewith and Manufacture Method thereof
US20190118341A1